Modulation of cholesterol efflux capacity in patients with myocardial infarction. (November 2019) - Silvain, Johanne; Kerneis, Mathieu; Guerin, Maryse; Montalescot, Gilles
Abstract : Purpose of review: Epidemiologic studies consistently demonstrated that patients with coronary artery disease (CAD) and low HDL cholesterol (HDL-C) are more likely to develop major adverse cardiovascular events as compared with those with normal or high HDL. However, several large randomized trials failed to demonstrate that a substantial, pharmacological-based, increase of HDL-C concentrations results in a clinically significant reduction of ischemic outcomes. This has been largely attributed to the fact that, although these drugs are able to raise the HDL-C concentration, they have no effect on HDL-C atheroprotective function. Subsequently, the 'HDL hypothesis' evolved, and the focus shifted from raising the concentration of HDL-C to raising the reverse cholesterol transport (RCT) function by increasing patients cholesterol efflux capacity (CEC) instead. Indeed, new data suggest that HDL-C metabolism and the ability of the HDL molecule to transport cholesterol from the atherosclerotic plaque to the liver, measured by the CEC, is more important than steady-state HDL-C levels. Modulation of the CEC has become, therefore, a promising therapeutic target in CAD patients. This article reviews the current data on the 'cholesterol efflux hypothesis' and discuss its ability to be modulated has a potential therapeutic target. Recent findings: Recent data have demonstrated that impaired serum CEC was associated with increased mortality after a myocardial infarction (MI). Thus, therapeutic intervention aiming to improve CEC and RCT may reduce the risk of recurrent events. Early phase clinical studies targeting CEC showed promising results and a megatrial is ongoing testing the hypothesis that an improved RCT trough a modulation of the CEC can modify patient's prognosis after an acute MI. Summary: The 'cholesterol efflux hypothesis' is now supported by several clinical studies and is being tested with a therapeutic candidate in a megatrial enrolling high-risk patient with MI.